Risk Management Practices and Performance: Evidence from Saudi Arabia Companies - Ben-Ahmed, Kais (International Journal of Membrane Science and Technology, 2023)
This paper scrutinizes the influence of risk management practices on Saudi financial companies' performance, as measured by accounting metrics, such as return on assets (ROA) and return on equity (ROE). The study focused on Saudi Arabia, an emerging nation, over twelve years (2010–2021). We collected financial and accounting variables data from the annual reports of ten financial companies listed on the Tadawul Stock Exchange in Saudi Arabia. We also obtained unavailable datasets from DataStream and Bloomberg. We followed the existing empirical literature, employed a panel-data approach, and formulated two equations using the Ordinary Least Square (OLS) estimator. The findings of this study revealed that bank size, total deposit, and credit-to-deposit ratio are vital for increasing the performance of Saudi banks. However, capital expenditure authorization negatively affects the performance of Saudi banks. Furthermore, loans have a negative impact on ROA but a positive effect on ROE. We also found that capital (CAP) has no significant association with the performance of Saudi banks in terms of ROE. This research is conducted in a less well-researched area, as limited studies have examined this question in Asian countries. However, like previous studies, it has limitations, such as a small sample size, limited variables, and study years. Future research should expand the sample size and extend the study to the Asian economic context. Better research and literature are much needed to understand the effects of other governance and control variables on financial companies' performance, particularly in emerging markets.